Labour after caesarean counselling documentation: a quality improvement intervention on labour and delivery - Elena Hill; Somphit Chinkam; Lilia Cardenas; Ronald Edward Iverson (BMJ Open Quality)
Background Most women who have had previous caesareans are eligible to have labour after caesarean (LAC), but only 11.9% do so. Studies show the majority of women have already decided about future mode of birth (FMOB) before a subsequent pregnancy. Hence, providing women with LAC counselling soon after birth may help women plan for future pregnancies. Prior to our intervention, our hospital had no method of ensuring that women received LAC counselling after caesarean section. The purpose of this QI initiative was to assess whether formal LAC documentation on labour and delivery (L&D) improves rates of LAC counselling post partum.Methods Our three-part intervention included: (1) surgeon’s assessment of LAC feasibility in the operative note, (2) written LAC education for women in discharge paperwork and (3) documentation of LAC counselling in the discharge summary. We implemented these changes on L&D in January 2019. We conducted phone surveys of 40 women after caesarean preintervention and postintervention. Surveys included questions regarding three primary outcomes: whether or not they had received LAC counselling either in the hospital or at a postpartum visit, and whether or not they would pursue LAC as FMOB. Surveys also assessed two secondary outcomes: (1) women’s understanding of the indications for surgery and (2) their involvement in the decision process. We used a χ2 analysis to assess primary outcomes and a Fisher’s exact test to assess secondary outcomes. We also surveyed providers about the culture of LAC counselling at our hospital.Results After our intervention, there was a significant difference between the number of women reporting LAC postpartum counselling (30.77% vs 53.8%, p=0.04). There was also a significant difference in the number of women feeling involved in the decision-making process (68% vs 95%, p=0.03). Providers reported improved knowledge/confidence around LAC counselling (58%–100%). Providers universally stated that LAC counselling has become more ingrained in the culture on L&D.Conclusions Documentation of LAC counselling improved the consistency with which providers incorporated LAC counselling into postpartum care. Addressing FMOB at the time of pLTCS and documenting that counselling may be an effective first step in empowering women to pursue LAC in future pregnancies.